Identification of Synthetic Food Colours in Selected Confectioneries and Beverages in Jaffna District, Sri Lanka - P. G. T. Dilrukshi; Helani Munasinghe; A. Buddhika G. Silva; P. G. S. M. De Silva (Journal of Food Quality)
Colour is a key component to enhance the ultimate appetizing value and consumer acceptance towards foods and beverages. Synthetic food colours have been increasingly used than natural food colours by food manufacturers to attain certain properties such as low cost, improved appearance, high colour intensity, more colour stability, and uniformity. Varied foods and beverages available in the market may contain some nonpermitted synthetic colours and overuse of permitted synthetic colours. This may lead to severe health problems such as mutations, cancers, reduced haemoglobin concentrations, and allergic reactions. According to the Food Act, 2011 (No. 26 of 1980), Sri Lanka, only nine synthetic food colours are permitted and the colour concentration cannot exceed 100 ppm as a single component or in combination. This study aims to identify the synthetic food colours in confectioneries and beverages available in Jaffna district, Sri Lanka. Randomly collected 110 samples from eleven Medical Officers Of Health areas in Jaffna district were analyzed by using thin layer chromatography and UV-visible spectrophotometry. According to the results, 100% beverages and 85% confectioneries contained permitted synthetic food colours. Out of all, 7% of the confectioneries did not contain any synthetic food colour and 8% of the confectioneries contained nonpermitted colours which do not comply with any of the permitted synthetic food colours. Tartrazine (E102) (41%) was the most used synthetic food colour in both confectioneries and beverages. Moreover, 60% of the beverages violated the label requirement without including proper colour ingredients. The study concluded that there is a high tendency to use synthetic food colours in confectioneries and beverages and some confectioneries contain unidentified colours including a textile dye. Therefore, the implementation of regulations and awareness programs of food colours for consumers and food manufacturers are highly recommended.